Who benefits the most from peer effects within ethnic group ? Empirical evidence on the South African Labour Market - (:unkn) unknown (My University, 2011)
This paper provides evidence that local social interactions within etnic groups may explain the puzzling variations in labour-market outcomes across individuals. Peer effects work first by creating pressure on labor-market participation, second, by conveying information about job opportunities and by raising wages. These effects differ through a selection effect : gender and ethnic groups who are less integrated in the labour market benefit more from peer effect. Finally, networks exhibit decreasing returns. The problems of endogeneity and simultaneity of local peer effects are addressed by using (i) data aggregated at the province level, (ii) the distribution of the sex of the peers' siblings as an instrumental variable and (iii) a quasi-panel data approach relying on the Hausman-Taylor estimator. The importance of social interactions in the labour market suggests that a social multiplier exists and our estimates show that any labour-market shock is magnified with an elasticity of 0.5.
Keywords: African Research